Systemic Lupus Erythematosus and Angioedema: A Cross-Sectional Study From the National Inpatient Sample - Yiming LUO,; Xiaowen FAN,; Changchuan JIANG,; Alvaro RAMOS-RODRIGUEZ,; Yumeng WEN,; Jianglin ZHANG,; Feng HUANG,; Xizhou GUAN,; Jiehui XU, (Archives of Rheumatology, 2019)
Objectives: This cross-sectional study aims to investigate the odds of developing angioedema (AE) in systemic lupus erythematosus (SLE) populations compared to non-SLE populations in hospital settings in the United States using a nationwide database. Materials and methods: We used the data from the National Inpatient Sample for the years 2012 to 2014. We constructed two models for multivariate logistic regression analysis. Model 1 was designed to adjust demographic information, while model 2 included each factor in model 1 and additionally accounted for AE-related comorbidities. Results: A total of 90,485 hospitalizations with an AE diagnosis were identified for the years 2012 to 2014, among which 1,505 hospitalizations had both SLE and AE. Compared to those without SLE, AE patients with SLE were younger and included more females. In AE hospitalizations, SLE was associated with higher odds of AE-related comorbidities including atopic disorder, leukocytoclastic vasculitis, eosinophilia, and infections. SLE was associated with higher odds of AE both as all inpatient diagnosis and as principal diagnosis (unadjusted odds ratio [OR] 3.24, 95% confidence interval [CI] 2.87-3.63, p<0.001, model 1 adjusted OR 2.54, 95% CI 2.26-2.86, p<0.001, model 2 adjusted OR 1.71, 95% CI 1.51-1.93, p<0.001). Conclusion: Our study demonstrates that SLE is associated with higher odds of having AE, including severe AE as the principal reason for inpatient admission. SLE is possibly an independent risk factor for AE.